Intestinal microbiota as biomarkers for different colorectal lesions based on colorectal cancer screening participants in community - Li, Gairui; Zhao, Dan; Ouyang, Binfa; Chen, Yinggang; Zhao, Yashuang (Frontiers in Microbiology, 2025)
IntroductionThe dysregulation of intestinal microbiota has been implicated in the pathogenesis of colorectal cancer (CRC). However, the utilization of intestinal microbiota for identify the lesions in different procedures in CRC screening populations remains limited.MethodsA total of 529 high-risk individuals who underwent CRC screening were included, comprising 13 advanced adenomas (Aade), 5 CRC, 59 non-advanced adenomas (Nade), 129 colon polyps (Pol), 99 cases of colorectal inflammatory disease (Inf), and 224 normal controls (Nor). 16S rRNA gene sequencing was used to profile the intestinal microbiota communities. The Gut Microbiota Health Index (GMHI) and average variation degree (AVD) were employed to assess the health status of the different groups.ResultsOur findings revealed that the Nor group exhibited significantly higher GMHIs and the lowest AVD compared to the four Lesion groups. The model incorporating 13 bacterial genera demonstrated optimal efficacy in distinguishing CRC and Aade from Nor, with an area under the curve (AUC) of 0.81 and a 95% confidence interval (CI) of 0.72 to 0.89. Specifically, the 55 bacterial genera combination model exhibited superior performance in differentiating CRC from Nor (AUC 0.98; 95% CI, 0.96-1), the 25 bacterial genera combination showed superior performance in distinguishing Aade from Nor (AUC 0.95). Additionally, the 27 bacterial genera combination demonstrated superior efficacy in differentiating Nade from Nor (AUC 0.82). The 13 bacterial genera combination exhibited optimal performance in distinguishing Inf from Nor (AUC 0.71).DiscussionOur study has identified specific microbial biomarkers that can differentiate between colorectal lesions and healthy individuals. The intestinal microbiota markers identified may serve as valuable tools in community-based CRC screening programs.